Social media and technopreneurial intention: a model based on technopreneur development - Mohd, Farahwahida; Shamsuddin, Norsila (Opción, 2019)
The objectives of this research are to determine the technopreneurial perception, attitude and belief on the technopreneurial intention. As a method, an administered survey level of technopreneurial intention and social media usage will be randomly distributed to Malaysian technopreneur and will be analyzed. In result, most of the respondents agreed that the Psychological Attributes do influence technopreneurial intentions with Attitudes has the highest agreeableness values, followed by self-efficacy and perceptions. As a conclusion, the respondents’ technopreneurial intentions are highly influences by their attitudes in using social media, followed by their self-efficacy and perception of other people surround